Иоганн Себастьян Бах - Махотин Сергей Анатольевич (Исторический роман, 2008)
Экземпляры: С/а ДБ (20101126) / Инвентарный номер: 96674 / Цена: 140 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: М 36 / ББК: 84(2Рос=Рус)6